Clinical Significance of Human Papillomavirus Genotype by Linear Array Assay in Japanese Women With Uterine Cervical Lesions and Type 16 Physical Status by In Situ Hybridization. Issue 8 (1st November 2009) - Futai, Mizuho; Watanabe, Jun; Jobo, Toshiko; Tsunoda, Shinpei; Nishimura, Yukari; Watanabe, Kayoko; Okayasu, Isao; Unno, Nobuya
Abstract : The aim of this study was to clarify the relation of human papillomavirus (HPV) genotypes and physical status in the cervical neoplasm of Japanese patients with the grade of the disease. Human papillomavirus genotype was detected using a linear array genotyping assay. Human papillomavirus status, diffuse or punctate signal pattern, was studied by biotynyl-tyramide-based in situ hybridization for positive cases of HPV-16. Human papillomavirus types 16, 52, 58, and 31, in descending order of frequency, were prevalent. The rates of HPV infection in patients with cervical intraepithelial neoplasia (CIN) or squamous cell carcinoma (SCC) were significantly higher than those in patients without cervical lesions. The frequency of HPV single infection in SCC was higher than that in CIN1 or CIN2. In an unspecified-risk HPV, types 66 and 70 were found in SCC and 62, 71, and 82 were detected in CIN3. The diffuse pattern was more frequent in CIN, and the punctate pattern was more frequent in SCC. Human papillomavirus types 16, 52, 58, and 31 were frequently detected in Japanese women with cervical neoplasias, and several unspecified-risk HPVs might be high-risk types. A single infection of HPV and a punctate signal pattern seemed to be closely correlated with cervical carcinogenesis.